The Impact of Health Swimming Program Management on Students' Physical and Mental Fitness - Agung Hilmi Wahdi; Kristi Agust (Journal Management of Sport, 2025)
Swimming is not only a competitive sport but also an effective intervention to improve physical and mental health. Despite its proven benefits, the integration of swimming into wellness programs in higher education is still limited, particularly in developing countries such as Indonesia. This study aimed to evaluate the effectiveness of an 8-week wellness swimming program on physical fitness and psychological well-being of sports education students at Riau University. A mixed-methods approach was used, incorporating quantitative data from 30 students (measured through the 12-minute Cooper Test, PSQI, DASS-21, and Likert scales) as well as semi-structured interviews with 5 participants. Quantitative results showed significant improvements in cardiovascular fitness (p < 0.01), sleep quality (p < 0.01), as well as decreased stress levels (p < 0.05) and daily fatigue (p < 0.01). Qualitative findings revealed increased energy, mental relaxation, and social support. The program was effective in improving physical and psychological health, supporting its integration into campus wellness initiatives. Colleges should consider swimming as a holistic wellness intervention, with the recommendation of continued research to explore long-term effects and scalability.